Local Democracy in the West-Nordic Countries - Grétar Þór Eyþórsson (Nordicum-Mediterraneum, 2020)
In 2012, the research project West Nordic municipal structure. Challenges to local democracy, efficient service provision and adaptive capacity was granted money from the Arctic Co-operation Programme 2012-2014. The overall aim of the project was to collect knowledge on the local level in the three West Nordic countries; the Faroe Islands, Greenland and Iceland by mapping the situation and development in the municipal sectors, focusing primarily on four aspects. The first was; the municipal structure. The second was; the democratic aspect – that is, which consequences the structural development has had for local democracy – to identify the main challenges to democracy, caused by the structural developments. The third; to map the service production capacity and effectiveness of the municipalities, and the fourth; to try to map the municipalities’ capacity to manage the development processes which often accompany municipal amalgamations. An overall research question was: What consequences have developments in municipal structure in the three countries had for democracy, local self-government and autonomy, as well as the ability to manage the processes accompanying amalgamations? In September 2014 a report containing this analysis was submitted . In this article I use the data from this survey to answer following main research questions: